Oral-Health-Related Quality of Life among Non-Syndromic School-Age Children with Orofacial Clefts: Results from a Cross-Sectional Study in Northern Italy - Patrizia Defabianis; Cesare Cogo; Stefania Massa; Federica Romano (MDPI AG, 2022)
The aim of this cross-sectional study was to determine the influence of orofacial clefts on the oral-health-related quality of life (OHRQoL) in a group of Italian children and adolescents and to examine whether gender, age, cleft type, and surgical protocol were associated with patients' OHRQoL. A total of 71 patients with cleft lip and/or cleft palate (CLP) and 71 age- and gender-matched controls (aged 8 to 18 years) were asked to complete the Child Oral Health Impact Profile (COHIP), a validated and reliable questionnaire to assess self-reported OHRQoL in children and teenagers. Children with orofacial clefts showed statistically significant lower quality of life scores than controls for total OHRQoL and for each of the subscales. Gender, the type of cleft, and the type of surgical protocol had no significant influence on OHRQoL. The negative impact of CLP on the area of self-image was greater in 12-18-year-olds, indicating a higher need for psychosocial counselling. These findings suggest that Italian CLP children and adolescents experience a poorer OHRQoL in comparison to their non-cleft peers.